The effect of diet supplemented with vegetable oils and/or monensin on the vaccenic acid production in continuous culture fermenters - Khattab, Mostafa Sayed A. (Anim Nutr, 2015)
Studies have shown that supplementing ruminant diets with vegetable oils modulated the rumen biohydrogenation and increased polyunsaturated fatty acid in their products. These positive values are often accompanied by a marginal loss of supplemented unsaturated fatty acids and rise in the concentrations of saturated fatty acids. This study were carried out mainly to investigate the effect of supplementing diets with sunflower oil, olive oil with or without monensin on the production and accumulation of vaccenic acid (VA) in continuous culture fermenters as a long term in vitro rumen simulation technique. Eight dual-flow continuous culture fermenters were used in an 8 replication experiment lasted 10 days each (first 7 days for adaptation and last 3 days for samples collection). Supplementing diets with plant oils and monensin in the present experiment increased VA and conjugated linoleic acids (P > 0.05) in ruminal cultures. The results suggest that supplementing diets with both olive oil and sunflower oil and monensin increased VA accumulation compared to plant oils supplemented alone without affecting the rumen dry matter and organic matter digestibility.